Detection toward early-stage thermal runaway gases of Li-ion battery by semiconductor sensor - Teng, Zhengfu; Lv, Cheng (Frontiers in Chemistry, 2025)
While achieving remarkable commercial success, lithium-ion battery (LIBs) carry substantial safety risks associated with potential thermal runaway during widespread applications. When operated under complex working conditions, particularly in high-temperature and high-pressure environments, the internal galvanic reactions within these batteries may escalate uncontrollably. During the early stages of LIBs thermal runaway, substantial amounts of characteristic gases such as H2, CO, and CO2 are released. Safety assess ent of current thermal runaway status can be achieved through detecting these indicative gas concentrations, thereby enabling efficient and safe utilization of LIBs. This study provides a mini review of current research on semiconductor sensors for detecting early characteristic gases in LIBs thermal runaway through two key dimensions. Firstly, the mechanisms governing the entire thermal runaway process are elucidated, with explicit analysis of gas generation patterns and detectable gas speciation. Subsequently, the review categorically examines research progress on sensors targeting four critical gas categories: carbon oxides, hydrogen, hydrocarbons, and volatile electrolytes. This work establishes a theoretical framework and technical reference for researchers in related fields to advance sensor development, while also providing actionable recommendations to facilitate the fabrication of high-performance sensing devices.